Pemberdayaan Kader Jumantik Desa Guwang Dalam Penggunaan Ekstrak Cempaka Kuning Sebagai Bahan Fogging Alami - Putu Indah Budi Apsari; Ni Wayan Widhidewi; Ni Wayan Winianti (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
The partners are 35 jumantik cadres from Guwang Village who are tasked with monitoring larvae and eradicating mosquito nests, especially those that act as vectors for dengue hemorrhagic fever. This service activity aims to increase the skills and knowledge of jumantik cadres in using the natural ingredient yellow cempaka extract as anti-mosquito fogging. The methods used in this service are counseling, training and demonstration. The results of this service are measured through pre-test and post-test. The conclusion is an increase in knowledge and skills of jumantik cadres in using natural fogging materials as mosquito repellent.